2022
DOI: 10.1002/mnfr.202200419
|View full text |Cite
|
Sign up to set email alerts
|

Association of Coffee and Tea Consumption with Cardiovascular Disease, Chronic Respiratory Disease, and their Comorbidity

Abstract: Scope Since associations between coffee and tea consumption with cardiovascular disease (CVD) and chronic respiratory disease (CRD) remain controversial. This study aims to investigate the separate and combined associations of coffee and tea consumption with CVD, CRD, and their comorbidity. Methods and results Within the UK Biobank, 390 039 participants (56.2 ± 8.1 years) free of CVD and CRD are included. Coffee and tea consumption are self‐reported at baseline. During a median follow‐up of 12.1 years, 31126 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…are processed to make tea, a fragrant herbal beverage consumed worldwide for refreshment and health. Indeed, drinking 2–3 cups of tea per day has been shown to be associated with lower morbidity of chronic respiratory diseases (Chen et al 2022b ). Moreover, the main active compounds in tea, including polyphenols, saponins, polysaccharides, and theanine, have anti-allergic properties (Li et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…are processed to make tea, a fragrant herbal beverage consumed worldwide for refreshment and health. Indeed, drinking 2–3 cups of tea per day has been shown to be associated with lower morbidity of chronic respiratory diseases (Chen et al 2022b ). Moreover, the main active compounds in tea, including polyphenols, saponins, polysaccharides, and theanine, have anti-allergic properties (Li et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of the substantial amount of caffeine in tea may cause cardiac arrhythmia ( Voskoboinik et al, 2019 ). So far, several studies reported that habitual tea intake may reduce the risk of CVD ( Wang et al, 2020 ; Niu et al, 2021 ; Chen et al, 2022 ). However, other observational studies suggested that tea consumption may be associated with a higher risk of CVD ( Malasevskaia et al, 2020 ; Feng et al, 2021 ; Zheng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic conditions are illnesses that develop gradually and need extended treatment and recovery [2]. Medically, chronic conditions are diseases with signs that last for longer than six months to over one year-such as Chronic Respiratory Disease (CRD) resulting from industrialization as a contagious illness [3]. Due to the growing geriatric population, the amount of seniors with chronic diseases has risen.…”
mentioning
confidence: 99%